1988
DOI: 10.1007/bf01311021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Rift Valley fever in rhesus macaques

Abstract: Rift Valley fever (RVF) is a major cause of human morbidity and mortality in endemic areas of sub-Saharan Africa and has the potential to cause epidemic disease in receptive areas world-wide. In this study, a RVF viral isolate from the 1977 Egyptian epidemic (ZH-501) inoculated intravenously into rhesus macaques caused a benign viremic infection in most, but resulted in the hemorrhagic fever syndrome in 20 per cent (3 of 15). Serious disease of this type has not previously been observed in nonhuman primates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 14 publications
3
70
1
Order By: Relevance
“…Indeed, several of the most promising replication-competent vaccine candidates lack NSs and are associated with an early systemic antiviral response (20) followed by a strong neutralizing antibody response correlating with protection from subsequent challenge with wild-type RVFV (18,(20)(21)(22)(23). These vaccine studies corroborate results from early passive transfer studies with nonhuman primates (24) and mice (25) that indicated protection from RVFV challenge is antibody mediated. However, little is known about how the host immune response influences clinical outcome during primary RVFV infection.…”
Section: Have Roles In Determining Virulence In Vivosupporting
confidence: 76%
“…Indeed, several of the most promising replication-competent vaccine candidates lack NSs and are associated with an early systemic antiviral response (20) followed by a strong neutralizing antibody response correlating with protection from subsequent challenge with wild-type RVFV (18,(20)(21)(22)(23). These vaccine studies corroborate results from early passive transfer studies with nonhuman primates (24) and mice (25) that indicated protection from RVFV challenge is antibody mediated. However, little is known about how the host immune response influences clinical outcome during primary RVFV infection.…”
Section: Have Roles In Determining Virulence In Vivosupporting
confidence: 76%
“…16 Autopsy samples from rhesus monkeys experimentally infected with RVFV displayed severe liver necrosis as the major microscopic finding. 17,18 Van der Lugt and others 19 studied the distribution of RVF viral antigens by immunoperoxidase in liver, spleen, lymph node, lung, and kidney of eight experimentally infected new-born lambs and four new-born lambs that died of RVF. Viral antigens were most prominent in the liver and were detected in the cytoplasm of hepatocytes at early stage of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The RVFV Gn and Gc glycoproteins are the major targets of protective immunity [17][18][19], therefore, the RVFV M segment, which encodes the Gn and Gc glycoproteins, as well as the non-structural protein nsM, was introduced behind the 26S promoter of the SIN-based replicons, as outlined in Figure 1. Correct orientation of the RVFV M segment was confirmed by restriction digest and by sequencing the full-length replicon/RVFV M segment constructs.…”
Section: Characterization Of Expressed Proteinsmentioning
confidence: 99%
“…The M segment RNA encodes a non-structural protein NSm of unknown function, plus a polyprotein precursor of the Gn and Gc glycoproteins which form the envelope peplomers that mediate binding and entry of virus into permissive cells [15,16]. The glycoproteins induce production of neutralizing antibody and protective immunity against infection with RVFV [17][18][19].…”
Section: Introductionmentioning
confidence: 99%